Three-year investigations on leaf rust of poplar cultivated for biomass production in Umbria, Central Italy - Covarelli, Lorenzo; Beccari, G.; Tosi, L.; Fabre, B.; Frey, P. (Pergamon, 2013)
During disease surveys carried out in the years 2006, 2007 and 2008, severe natural rust infections on biomass poplar cultivations in clone experimental field trials in the province of Perugia (Umbria, Central Italy) were observed both in summer and autumn. The foliage of infected plants presented the typical rusty coloration for the presence of uredinia, mainly on the abaxial leaf surface, and teliospores which appeared at the end of the growing season. All tested clones showed to be susceptible to the disease, with significant incidence and severity differences among them. Clones 'Sirio', 'Baldo' and 'AF8' showed a lower susceptibility with respect to the other clones. Weather data suggested that the early summer attacks observed in 2008 were favored by the high rainfalls recorded in June and by the possible presence of asexual spores which were able to overwinter on infected leaf residues. Microscopic observations of the morphological characteristics of pathogen spores, the examination of infected leaf sections, species-specific PCR assays, and pathotype identification revealed that the recorded rust attacks were caused by the species Melampsora larici-populina (pathotype 2-4) and Melampsora allii-populina. This represents a comprehensive study on the occurrence of poplar leaf rust in central Italy, an area where poplar short rotation coppice (SRC) could potentially increase in the next years. © 2013 Elsevier Ltd.